2010
DOI: 10.1258/phleb.2010.010030
|View full text |Cite
|
Sign up to set email alerts
|

Venous gas embolism during foam sclerotherapy of saphenous veins despite recommended treatment modifications

Abstract: Bubble emboli entered the heart during foam UGS of saphenous veins despite all treatment modifications and low volumes of foam used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 33 publications
2
43
1
Order By: Relevance
“…155 However, in a recent study by the author, CO 2 bubbles arrived in the right heart within 60 seconds and continued for another 25 minutes following a single injection of 2.5 mL of sclerosant foam in a small saphenous vein. 109 Similar findings have been reported by Morrison et al 150 Total volume of sclerosant Neurological symptoms are reported with as little as 20 mL of air injected intravenously. 106 In humans, an intravenous injection of 200-300 mL of air (5 mL/kg) has been fatal.…”
Section: Sclerosant Concentrationsupporting
confidence: 81%
See 3 more Smart Citations
“…155 However, in a recent study by the author, CO 2 bubbles arrived in the right heart within 60 seconds and continued for another 25 minutes following a single injection of 2.5 mL of sclerosant foam in a small saphenous vein. 109 Similar findings have been reported by Morrison et al 150 Total volume of sclerosant Neurological symptoms are reported with as little as 20 mL of air injected intravenously. 106 In humans, an intravenous injection of 200-300 mL of air (5 mL/kg) has been fatal.…”
Section: Sclerosant Concentrationsupporting
confidence: 81%
“…Bubbles are observed to enter the right heart following the injection of 1 -2.5 mL of the sclerosant foam. 109 In a recent study, manual compression or ligation of the saphenofemoral junction did not prevent, but reduced the flow of foam into the femoral vein. 162 In a study by the author, once the junction was occluded by the initial foam injection, subsequent injections in the proximal trunk of the great saphenous vein (GSV) did not result in further systemic embolization of bubbles.…”
Section: Sclerotherapy Techniquesmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, an even higher prevalence of RLS of 58.9 % has been reported in patients with symptomatic GSV incompetence [26]. After UGFS, gas bubbles have been shown to enter the right heart in most patients [27], and may be detected in brainsupplying arteries in ¾ of patients in presence of a RLS [20,24]. Fusion of several bubbles to form bubbles large enough to occlude intracranial arteries or bubble-induced vasospasm followed by activation of the coagulation system have been suggested to be responsible for a number of post-sclerotherapy strokes occurring within few minutes after foam sclerotherapy [20].…”
Section: Discussionmentioning
confidence: 99%